Chinese poetry in times of mind, mayhem and money - Crevel, Maghiel van (Sinica Leidensia, 2008)
Covers a range of contemporary authors and issues, from Haizi to Yin Lichuan and from poetic rhythm to exile-bashing. This book is organized around the notions of text, context and metatext, meaning poetry, its socio-political and cultural surroundings, and critical discourse in the broadest sense.